Impact of Weather Factors on Unmanned Aerial Vehicles’ Wireless Communications - Lalan Mishra; Naima Kaabouch (Future Internet)
As the applications of unmanned aerial vehicles (UAV) expand, reliable communication between UAVs and ground control stations is crucial for successful missions. However, adverse weather conditions caused by atmospheric gases, clouds, fog, rain, and turbulence pose challenges by degrading communication signals. Although, some recent studies have explored the nature of signal attenuation caused by atmospheric weather variations, studies that compare the attenuation from various weather conditions and analyze the effect on available bandwidth are missing. This work aimed to address this research gap by thoroughly investigating the impact of atmospheric weather conditions on the bandwidth available for UAV communications. Quantitative and qualitative performance analyses were performed for various weather conditions using metrics such as attenuation and the bit error rate of the received signals associated with different modulation schemes and frequencies, using a linearly segmented attenuation model. The results indicate that atmospheric gases and clouds/fog affect wireless signal propagation; however, the effect of rain on the propagation distances and operating frequencies considered in this study was the most severe. Based on the influence of power transmission, operating frequency, modulation schemes, distance, and adverse weather conditions on the bit error rate and bandwidth suboptimization, we propose an algorithm to select the maximum operating frequency for reliable UAV link operation.